ANALYSIS OF FACTORS AFFECTING THE APPROVAL OF MICRO, SMALL AND MEDIUM ENTERPRISES CREDIT APPLICATIONS AT PEER TO PEER LENDING FINANCING INSTITUTIONS DURING THE COVID-19 PERIOD - Savitri, Aziza; Nikensari, Sri Indah; Suparno (Faculty of Economics and Business, Universitas Negeri Jakarta, 2022)
MSMEs are one of the boosters of the Indonesian economy because they are considered to have a large contribution to economic growth. However, since the emergence of the COVID-19 virus, of course, it has an impact on MSMEs, in 2020 the economic growth figure shows a figure of minus 5.3 percent and there are 37,000 MSMEs affected by COVID-19, so the obstacle faced by MSMEs is the need for capital to rise in the midst of the COVID-19 pandemic. The purpose of this study is to find out what factors influence the approval of MSMEcredit applications to peer to peer lending institutions during the COVID-19 period. The method used is probit regression analysis with the IBM SPSS Statistics 25 application. The independent variables used in the study were the amount of loan, length of business andcredit period.The results of this study found that the loan amount and credit period have a negative and insignificant influence on the approval of credit applications, while the length of business has a positive and significant influence on the approval of credit applications.